Esperanto - lingua franca and language community - Fiedler, Sabine 1957-; Brosch, Cyril 1981- (John Benjamins Publishing Company, 2022)
"This book addresses a fascinating topic - a constructed language that has turned from a project into a fully-fledged language used by some of its speakers on a daily basis. Based on extensive fieldwork, this book provides rare and profound insights into the use of Esperanto in a large number of communicative areas. It studies the speakers' use of code-switching, phraseology and metaphors, techniques they employ to enhance understanding, such as metacommunication and repair strategies, as well as their predilection for humour. The study also contributes to a comparison between the communication in Esperanto and in the language that is now predominantly used as a lingua franca - English - and allows conclusions to be drawn on the question of what a lingua franca is all about"
Includes bibliographical references and index
Keywords: Gesprochene Sprache; Kommunikation; Esperanto; Esperanto / Spoken Esperanto; Esperanto / Usage; Esperanto / Social aspects